DEPLOYMENT OF GYM WORK: A CASE STUDY OF MAGISTRATES PROFILE/ SERVERS REGIONAL LABOUR COURT 19th REGION ALAGOAS. (Fiep Bulletin - online, 2013)
The Gymnastics began to be understood as a major tool in improving the physical health of the employee reducing and preventing occupational problems. For (HARTMANN et ali, 2008). The Regional Labor Court of Alagoas 19th Region concerned about the welfare of mankind in all its aspects, seeks to provide response mechanisms to prevent and minimize the consequences of various postural defects, injuries, occupational repetitive strain (RSI), structures that are degenerative and cumulative preceded by any pain or discomfort and even work-related disorders (MSDs), since we are aware that the body can not be separated from the mind, as it will only be complete and in full harmony, if running perfectly as a whole, in a single unit. Objective: This study aimed to identify the profile of magistrates/servers Regional Labor Court of the 19th Region of Alagoas. Methods: The sample consisted of 156 magistrates / servers Building Bridges Miranda in Maceió-AL. Of these, 82 were male and 74 representing 53% female 47%. Of the 156 who responded to the questionnaires servers 82 are of an age between 20 to 64 years old, with mean = 41.34 years, and 74 are of an age group between 25 and 62 years old, with mean = 39.95 years . After review and discussion of the results it was found that the magistrates / servers Regional Labor Court 19 th Region of Alagoas are within international standards when compared with the scale of flexibility, according to (AMERICAN MEDICAL ASSOCIATINON, 1995) now with respect to variable handgrip strength they need the intervention of gymnastics, so you can better the level of manual force. We suggest a program of gymnastics where they give emphasis strength and flexibility of the wrist joint.
Keywords: Gymnastics; Profile; RSI